Peran Kelompok Tani dalam Pemanfaatan Limbah Kotoran Ternak Sapi: Penelitian - Nabila Uswatun Hasna; R. Hermawan; RR Siti Astuti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aimed to ascertain the contribution of farmer groups, operating as learning platforms, cooperation forums, and production units, in the utilization of cattle manure waste in Dusun Beji, Kalurahan Beji, Kapanewon Patuk, Gunungkidul Regency. The study location was selected through purposive sampling, given that Kalurahan Beji constituted the largest area and harbored the highest cattle population among comparable administrative units. The Rukun Agawe Makmur Farmer Group was also chosen purposively, as it had been the only group to obtain 'primary class' status in Kalurahan Beji. Sampling was carried out using simple random sampling, and the sample size was determined according to Krejcie and Morgan’s table, resulting in fifty-six respondents. Data were analyzed employing quantitative descriptive techniques and multiple linear regression. The results revealed that the roles of the farmer groups as learning platforms and cooperation forums were categorized as very influential; however, they did not significantly influence the utilization of livestock waste. Conversely, their role as a production unit was classified as influential and had exerted a significant effect on waste utilization. Consequently, to enhance the utilization of livestock waste among farmers in Kalurahan Beji, sustained technical assistance and capacity-building in manure processing were required.